The art of fighting under glass - Daniel Jaquet (Bern Open Publishing, 2018)
A growing body of research on fight books and historical European martial arts has appeared in academic circles over the last fifteen years. It has also broken through the doors of patrimonial institutions. From curiosities in exhibitions about knighthood, to dedicated temporary exhibitions about historical European martial arts, the fight books have received more and more attention from museum professionals. This article attempts to present an exhaustive list of fight books displayed in museum exhibitions over the last fifty years. It then proposes a critical view about how and why they were displayed from the perspective of the curators, based on a review of the exhibition catalogues.